2014
DOI: 10.1210/jc.2013-1956
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Adiposity in Cushing Syndrome Caused byPRKAR1AMutations: Clues for the Role of Cyclic AMP Signaling in Obesity and Diagnostic Implications

Abstract: Increased PKA signaling in PAT was associated with lower BMI in CS. Differences in fat distribution may contribute to phenotypic differences between patients with CS with and without PRKAR1A mutations. The observed differences are in agreement with the known roles of cAMP signaling in regulating adiposity, but this is the first time that germline defects of PKA are linked to variable obesity phenotypes in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Recently, it has been shown that patients with CS due to primary pigmented nodular adrenal disease have a typically milder obese phenotype than other forms of CS, even when their cortisol levels are comparable and their CS is not atypical or cyclical (108). The authors speculate that patients with CS due to perturbations of the cAMP/PKA pathway may be less obese because of increased PKA activity and resulting altered downstream regulation of cAMP-related lipogenic and lipolytic proteins (109).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Recently, it has been shown that patients with CS due to primary pigmented nodular adrenal disease have a typically milder obese phenotype than other forms of CS, even when their cortisol levels are comparable and their CS is not atypical or cyclical (108). The authors speculate that patients with CS due to perturbations of the cAMP/PKA pathway may be less obese because of increased PKA activity and resulting altered downstream regulation of cAMP-related lipogenic and lipolytic proteins (109).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…All demographic data and diagnoses of the primary cohort of patients for which tissue samples were available and in vitro studies were performed have been described [ 1 ] . See • ▶ Table 1 for a summary of patients included by diagnostic group.…”
Section: Diagnostic and Anthropometric Data Demonstrated Diff Erencesmentioning
confidence: 99%
“…BAHs are a heterogeneous group of disorders roughly divided in half in terms of frequency and age-distribution: massive macronodular adrenocortical disease (MMAD, also known as ACTHindependent macronodular hyperplasia or AIMAH) with lesions larger than 1 cm is more frequent in older adults [ 6 ] , whereas micronodular forms of BAH, in which the lesions are smaller than 1 cm, are more frequent in children and young adults [ 7 ] . Micronodular BAH is further subdivided into a relatively more frequently pigmented variant, primary pigmented nodular adrenocortical disease (PPNAD) [ 8 ] , and the more recently described [ 9 ] isolated micronodular adrenocortical disease (iMAD), which does not have signifi cant or any pigmentation in its histology but shares all other features with PPNAD Introduction ▼ We recently published analysis of data from the same cohorts of patients presented here that compared phenotypic characteristics based on the presence or absence of PRKAR1A mutation in patients with Cushing syndrome (CS) [ 1 ] . Here, we have reanalyzed all data collected pre-operatively and extended this work and the in vitro experiments in periadrenal adipose tissue (PAT) to describe phenotypic diff erences between the diff erent forms of CS and to propose mechanisms for observed phenotypes based on diff erences in cAMP/PKA signaling.…”
mentioning
confidence: 99%
See 2 more Smart Citations